Prevalência de cárie dentária na adolescência em Belém do Pará: uma perspectiva amazônica: Prevalence of dental caries in adolescence in Belém do Pará: an amazon perspective - Conde Barros, Wallace Rafael; do Nascimento, Liliane Silva; da Cunha Fontes, Rosely Barbosa; Lima Aguiar, Natália; da Silva Júnior, Ivam Freire; da Silva Júnior, Ivam Freire; Pamplona de Souza, Cristiane Nazaré (Adolescência e Saúde, 2015)
Objective: This study aims to collect data to estimate the prevalence of dental caries in adolescents in the city of Belém, Pará, Brazil, using the variables age, gender, oral hygiene and access to dental services, contributing to actions for health promotion and disease prevention. Methods: This is a descriptive observational study of quantitative characteristics. Data collected consisted of a systematic sample of 480 adolescents who responded to questionnaires about oral hygiene habits and underwent examinations using the index of decayed, missing and fi lled teeth (DMFT) to assess the oral health status. Results: The prevalence of DMFT index in adolescents was 58.54% and the DMFT average index 2.08, which is above the national and regional average of the latest epidemiological survey. The carious component accounted for most of the DMFT index (81.85%), demonstrating the lack of access to dental care in this population. The highest values of DMFT index were observed in older female, however both factors were not statistically signifi cant for the presence of the disease. The frequency of dental appointments proved to be a decisive factor for the presence or absence of decayed teeth. Conclusion: These data suggest a lack of restorative dental treatment and alarming prevalence of teeth affected by dental caries, indicating the need for action to promote oral health, in order to minimize the complications caused by the disease, thus improving the adolescents’ quality of life.